Management of Children with Disease Caused by New Coronaviral Infection (SARS-CoV-2) - Yurii S. Alexandrovich; Elena N. Baybarina; Alexander A. Baranov; Elena A. Vishneva; Nadezda N. Zvereva; Dmitry O. Ivanov; Daria S. Kruchko; Ivan V. Konovalov; Tatiana V. Kulichenko; Yuri V. Lobzin; Ludmila N. Mazankova; Leyla S. Namazova-Baranova; et al. (Педиатрическая фармакология, 2020)
The Ministry of Health of the Russian Federation jointly with professional association and experts in the field of pediatrics, infectious diseases and resuscitation has developed guidelines “Clinical Features and Management of the Disease Caused by New Coronaviral Infection (COVID-19) in Children” in order to provide the child population with effective medical care during the pandemic of the new coronaviral infection. The practical experience of specialists from various countries was considered during the development of this document. Special attention should be given to the evidence base of the presented data, as well as to the efficiency and safety issues of medications used in treatment of coronaviral infection and its complications. The authors highlight the problems of prevention, diagnostics and management of pathological conditions caused by COVID-19 in the article according to the presented guidelines. Patient’s management is presented depending on the age and severity of the disease itself. The therapy is considered with regard to etiological, pathogenetic and symptom focus.